2020
DOI: 10.3390/ijerph17144977
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Palliative Care Consultation Service (PCCS) in an Acute Hospital Setting

Abstract: Background and study aims: Acute health service requires focused palliative care (PC). This study was performed to provide guidance for the establishment of a palliative care consultation service (PCCS). Patients and methods: This study was conceived as a retrospective single-center study for observing, analyzing and evaluating the initial setup of a PCCS from 1 May 2015 to 31 May 2018. Patients from Muenster University Hospital with advanced life-limiting diseases, identified to require PC, were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Multiple palliative care services have been initiated in recent years, including inpatient care in palliative care unit [ 15 ], palliative home care service [ 16 ] and palliative care consultation service (PCCS) [ 17 ]. A previous study has shown that PCCS during hospitalization for cancer patients can improve patients’ and families’ awareness of disease diagnosis and prognosis, and also increase consent to DNR [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple palliative care services have been initiated in recent years, including inpatient care in palliative care unit [ 15 ], palliative home care service [ 16 ] and palliative care consultation service (PCCS) [ 17 ]. A previous study has shown that PCCS during hospitalization for cancer patients can improve patients’ and families’ awareness of disease diagnosis and prognosis, and also increase consent to DNR [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Albeit pain was the main problem for all patients when VR intervention was performed, initial contact with specialized PC resulted due to pain (57.5%, n = 23), organization of outpatient care (35%, n = 14), and complexity of care in ICU/isolation (7.5%, n = 3). Patients were treated by the PCCS according to their actual needs and under the consideration of our treatment algorithm [15]. Variations among the participants regarding their need for supportive care are also apparent in days of PCCS cocare, which ranged between 1 and 245 days (29 ± 41.18).…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…The proportion of PC patients suffering from pain is quantified to be 64% according to another survey [14]. Looking at inpatients who were treated by the Palliative Care Consultation Service (PCCS) at Muenster University Hospital between May 1, 2015 and May 31, 2016, 56.7% (278 of 490) were affected by pain (measured with visual analog scale, mean 5.1, SD 2.7, median 5.0) [15]. Observational research confirms that many patients suffering from cancer experience moderate or severe pain yet do not receive appropriate treatment [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…A wide spectrum of patient populations was included, ranging from cancer patients to noncancer patients and older adults with moderate–severe physical impairment and cognitive frailty. Engel and colleagues [ 4 ] reported the establishment of a palliative care consultation service in an acute hospital in Germany. This palliative care consultation team supports physicians and nurses by providing medication recommendations for their patients.…”
Section: Included Workmentioning
confidence: 99%